High-Risk Contexts for Violence Against Women: Using Latent Class Analysis to Understand Structural and Contextual Drivers of Intimate Partner Violence at the National Level - Brown, Laura J (Journal of interpersonal violence, 2023)
Introduction: Intimate partner violence (IPV) affects 1 in 3 women and poses a major human rights threat and public health burden, yet there is great variation in risk globally. Whilst individual risk factors are well-studied, less research has focussed on the structural and contextual drivers of IPV and how these co-occur to create contexts of high risk. Methods: We compiled IPV drivers from freely-accessible global country-level data sources and combined gender inequality, natural disasters, conflict, colonialism, socioeconomic development and inequality, homicide and social discrimination in a latent class analysis, and identified underlying ‘risk contexts’ based on fit statistics and theoretical plausibility (N=5,732 country-years; 190 countries). We used multinomial regression to compare risk contexts according to: proportion of population with disability, HIV/AIDS, refugee status, and mental health disorders; proportion of men with drug use disorders; men’s alcohol consumption; and population median age (N=1,654-5,725 country-years). Finally, we compared prevalence of physical and/or sexual IPV experienced by women in the past 12 months across risk contexts (N=3,175 country-years). Results: Three distinct risk contexts were identified: 1) non-patriarchal egalitarian, low rates of homicide; 2) patriarchal post-colonial, high rates of homicide; 3) patriarchal post-colonial conflict and disaster-affected. Compared to non-patriarchal egalitarian contexts, patriarchal post-colonial contexts had a younger age distribution and a higher prevalence of drug use disorders, but a lower prevalence of mental health disorders and a smaller refugee population. IPV risk was highest in the two patriarchal post-colonial contexts and associated with country income classification. Conclusions: Whilst our findings support the importance of gender norms in shaping women’s risk of experiencing IPV, they also point towards an association with a history of colonialism. To effectively address IPV for women in high prevalence contexts, structural interventions and policies are needed that address not only gender norms, but also broader structural inequalities arising from colonialism.